Development of a sensitive liquid-liquid extraction method for the determination of N-butyryl-L-homoserine lactone produced in a submerged membrane bioreactor by gas chromatography mass spectrometry and deuterated anthracene as the internal standard - Bakaraki, Nouha; Chormey, Dotse Selali; Bakirdere, Sezgin; Engin, Guleda Onkal (ROYAL SOC CHEMISTRY, 2016)
Quorum sensing is defined as the bacterial communication through sending and receiving chemical signals such as N-acyl homoserine lactone (AHL) and oligopeptide for Gram negative bacteria and Gram positive bacteria, respectively. This mysterious bacterial interaction regulates a wide range of activities affecting the environment, agriculture, and therefore, humans. In the last century, quorum sensing investigations trying to follow and measure these chemical signals have accelerated. In this study, an analytical method was developed and optimized in order to extract and measure one of the AHLs: N-butyryl-L-homoserine lactone (C4-HSL) by gas chromatography-mass spectrometry (GC-MS). The aim of the study was to develop a method that increases the sensitivity and precision of AHL detection by GC-MS due to the problem in the determination of analytes in wastewater which have a complex matrix. The limits of detection and quantification obtained for C4-HSL were 12.9 ng mL(-1) and 43.3 ng mL(-1), respectively. The precision of the method was improved upon using deuterated anthracene as the internal standard, which gave a lower relative standard deviation compared to that without the internal standard.
Keywords: SOLID-PHASE EXTRACTION; SENSING SIGNAL MOLECULES; ACYLHOMOSERINE LACTONES; CHROMOBACTERIUM-VIOLACEUM; PSEUDOMONAS-AERUGINOSA; QUANTIFICATION; MICROEXTRACTION; PURIFICATION; BACTERIA; MODEL; Chemistry; Food Science & Technology; Spectroscopy